2011
DOI: 10.1016/j.biomaterials.2010.09.044
|View full text |Cite
|
Sign up to set email alerts
|

A functionalizable reverse thermal gel based on a polyurethane/PEG block copolymer

Abstract: Injectable reverse thermal gels have great potentials as biomaterials for tissue engineering and drug delivery. However, most existing gels lack functional groups that can be modified with biomolecules that can guide cell/material interactions. We created an amine-functionalized ABA block copolymer, poly(ethylene glycol)-poly(serinol hexamethylene urethane), or ESHU. This reverse thermal gel consists of a hydrophobic block (B): poly(serinol hexamethylene urethane) and a hydrophilic block (A): poly(ethylene gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
85
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 63 publications
1
85
0
Order By: Relevance
“…Previously, we have demonstrated that an aqueous solution of ESHU will undergo a sol-to-gel phase transition when the temperature is increased from room to body temperature, making it attractive for minimally invasive applications. 18 We hypothesized that ESHU would be a suitable platform for intraocular drug delivery and demonstrated that it is compatible with cells from ocular sources, and capable of releasing bevacizumab over a 17-week period in vitro. 19 The aim of the present study was to demonstrate sustained bevacizumab release in vivo when compared to a standard, bolus injection.…”
mentioning
confidence: 99%
“…Previously, we have demonstrated that an aqueous solution of ESHU will undergo a sol-to-gel phase transition when the temperature is increased from room to body temperature, making it attractive for minimally invasive applications. 18 We hypothesized that ESHU would be a suitable platform for intraocular drug delivery and demonstrated that it is compatible with cells from ocular sources, and capable of releasing bevacizumab over a 17-week period in vitro. 19 The aim of the present study was to demonstrate sustained bevacizumab release in vivo when compared to a standard, bolus injection.…”
mentioning
confidence: 99%
“…This is an attractive property, especially for drug delivery, because it allows for controlled degradation. Another quality is that PEG gels can be modified to be thermally activated so that they are liquid at room temperature but quickly gel in situ [118] . Due to its hydrophilic properties, PEG has been useful in repairing damaged neuronal membranes when applied directly to the injury site immediately following a crush injury [119][120][121][122] , in a delayed application [123] , or as a subcutaneous application [124] .…”
Section: Poly-ethylene-glycol (Peg)/poly-ethylene Oxide (Peo)mentioning
confidence: 99%
“…PEG is favorable as it is functionalizable and groups have incorporated cell-binding domains such as RGD [125] and iKVAV [126] . it can be used for cell immobilization [127] and drug release [128] .…”
Section: Poly-ethylene-glycol (Peg)/poly-ethylene Oxide (Peo)mentioning
confidence: 99%
See 1 more Smart Citation
“…Biodegradable polyurethanes can be engineered into different physical forms as drug carriers, such as nanoparticles (Wang, Gao et al 2013), microspheres (Subhaga, Ravi et al 1995), micelles (Yu, Ding et al 2014), films ), gels (Park, Wu et al 2011), or scaffolds (Hafeman, Zienkiewicz et al 2010). Therapeutic agents can be loaded into these formulations by many methods, such as casting, oil-in-water emulsion/solvent evaporation, covalent link to polyurethane chains and adsorption.…”
Section: Biodegradable Polyurethanes As Drug Delivery Systemsmentioning
confidence: 99%